The use of new technologies for nutritional education in primary schools: a pilot study. (November 2016) - Rosi, A.; Dall'Asta, M.; Brighenti, F.; Del Rio, D.; Volta, E.; Baroni, I.; Nalin, M.; Coti Zelati, M.; Sanna, A.; Scazzina, F.
Abstract: Introduction: The aim of this study was evaluating if the presence of a humanoid robot could improve the efficacy of a game-based, nutritional education intervention. Study design: This was a controlled, school-based pilot intervention carried out on fourth-grade school children (8–10 years old). A total of 112 children underwent a game-based nutritional educational lesson on the importance of carbohydrates. For one group ( n = 58), the lesson was carried out by a nutritional educator, the Master of Taste (MT), whereas for another group, ( n = 54) the Master of Taste was supported by a humanoid robot (MT + NAO). A third group of children ( n = 33) served as control not receiving any lesson. Methods: The intervention efficacy was evaluated by questionnaires administered at the beginning and at the end of each intervention. The nutritional knowledge level was evaluated by the cultural-nutritional awareness factor (AF) score. Results: A total of 290 questionnaires were analyzed. Both MT and MT + NAO interventions significantly increased nutritional knowledge. At the end of the study, children in the MT and MT + NAO group showed similar AF scores, and the AF scores of both intervention groups were significantly higher than the AF score of the control group. Conclusions: This study showed a significant increase in the nutritional knowledge of children involved in a game-based, single-lesson, educational intervention performed by a figure that has a background in food science. However, the presence of a humanoid robot to support this figure's teaching activity did not result in any significant learning improvement. Highlights: Schools are an optimal place for nutrition education. Game-based lessons and new technology, such as robots, can improve children's engagement. This study trialled the use of a robot in addition to a game-based nutrition lesson. The lesson enhanced children's knowledge, but the robot did not improve outcomes. A larger, more detailed trial is required to confirm the findings.